La nueva administración estadounidense y su impacto en la relación bilateral con México - Ostos Cetina, María del Pilar (2017)
The purpose of this essay is to reflect on the state of current relations between Mexico and the United States after the rise of President Donald Trump, which has had a significant media impact, which in turn has influenced the posture which have assumed the leaders of both countries; which has encouraged nationalist claims and the trend toward economic protectionism, as evidenced in the American case through the content of America First’s discourse and praxis. At the same time, there have been several expectations of change or continuity with regard to addressing the priority issues on the bilateral agenda, beginning with the effects on the expansion of the border «containment» wall in the face of massive influx of immigrants, The development of the North American Free Trade Agreement (NAFTA), as well as aspects related to national security issues from the fight against drug cartels and the neutralization of organized crime, whose effects go beyond the bilateral to hemispheric issues.